Question about Office Equipment & Supplies

I calculators __you can't__ change or set the base of 'log' is __default 10__ so you need to know these:

log x (base y) = log x / log y

when log x it's automatic log x (base 10) here some examples:

log 8 (base 2) = log 8 / log 2

log 27 (base 3) = log 27 / log 3

and the base it's default 10 again, and that is how you need to use it in calculators(no bases), and here the explanation to this:

log x (base y) = log x (base 10) / log y (base 10) = (log x / log 10) / (log y / log 10) = (log x / log 10) * (log 10 / log y) = log x / log y

here so other stuff about 'log' :

log (x*y) = log x + log y

log (x/y) = log x - log y

Hope it's helped**☺**

log x (base y) = log x / log y

when log x it's automatic log x (base 10) here some examples:

log 8 (base 2) = log 8 / log 2

log 27 (base 3) = log 27 / log 3

and the base it's default 10 again, and that is how you need to use it in calculators(no bases), and here the explanation to this:

log x (base y) = log x (base 10) / log y (base 10) = (log x / log 10) / (log y / log 10) = (log x / log 10) * (log 10 / log y) = log x / log y

here so other stuff about 'log' :

log (x*y) = log x + log y

log (x/y) = log x - log y

Hope it's helped

on Jul 07, 2009 | Casio fx-300ES Calculator

Jan 14, 2017 | Computers & Internet

go to the main or home page. look for "Log In", you will then be prompted for a password.

Nov 11, 2013 | Computers & Internet

I really into 'Muscle Gainer' app. It is really good.Introducing the Muscle Gainer, the ultimate and the only weight gainer on the store specially created for bodybuilders.

Muscle Gainer is a powerful protein tracker. At all levels of experience, bodybuilders should consume at least a gram of protein per pound of body weight each day.

Muscle Gainer is a powerful protein tracker. At all levels of experience, bodybuilders should consume at least a gram of protein per pound of body weight each day.

Sep 06, 2010 | iPhone Apps

Hi,

It is easier to use the rules for logarithms to clean this equation before trying to solve it. And the calculator is no help here.

Let me represent the logs as follows log b in base a = log(a,b). The first argument is the base.

2*log(4,x) - log(4,3)= log(4,x)- log(4,2)

Here you have two similar terms 2*log(4,x) on the left and log(4,x) on the right. Gather them both on the same side, say the left. You have

**2*log(4,x) -log(4,x) +log(4,3) = log(4,x)-log(4,x) -log(4,2) **

which is equivalent to**log(4,x) +log(4,3) = -log(4,2)**

Gather the constant terms on the right, and use log(a) +log(b)=log(a*b)

log(4,x) = -log(4,2) -log(4,3) =**- { log(4,2)+log(4,3)}** = -log(4,2*3)

You get**log(4,x)= -log(4,6)**.

Take the constant term to the left, while changing its sign in the process. On the right remains 0, which is also the log of 1 in any base So log(4,x)+log(4,6) =0 =log(4,1)

Use the rule log(a) +log(b) = log(a*b) valid in any base, to obtain

log(4,6x)=log(4,1) which is equivalent to 6x=1. The solution is x=1/6

There are a few other shortcuts to get the solution but I preferred to take a pedestrian, step by step, approach.

Hope it helps.

It is easier to use the rules for logarithms to clean this equation before trying to solve it. And the calculator is no help here.

Let me represent the logs as follows log b in base a = log(a,b). The first argument is the base.

2*log(4,x) - log(4,3)= log(4,x)- log(4,2)

Here you have two similar terms 2*log(4,x) on the left and log(4,x) on the right. Gather them both on the same side, say the left. You have

which is equivalent to

Gather the constant terms on the right, and use log(a) +log(b)=log(a*b)

log(4,x) = -log(4,2) -log(4,3) =

You get

Take the constant term to the left, while changing its sign in the process. On the right remains 0, which is also the log of 1 in any base So log(4,x)+log(4,6) =0 =log(4,1)

Use the rule log(a) +log(b) = log(a*b) valid in any base, to obtain

log(4,6x)=log(4,1) which is equivalent to 6x=1. The solution is x=1/6

There are a few other shortcuts to get the solution but I preferred to take a pedestrian, step by step, approach.

Hope it helps.

Nov 25, 2009 | Casio FX-300MS Calculator

It's simple here some logs:

log x base y = log x / log y

log (x*y) = log x + log y

log (x/y) = log x - log y

you just need to know that the default base of log in calculators is 10, so log x mean

log x base 10 = log x / log 10,

so write log x / log y for log x base y example:

log 8 base 2 = log 8 / log 2 that is how you write it on calculator, hope it was helpful

log x base y = log x / log y

log (x*y) = log x + log y

log (x/y) = log x - log y

you just need to know that the default base of log in calculators is 10, so log x mean

log x base 10 = log x / log 10,

so write log x / log y for log x base y example:

log 8 base 2 = log 8 / log 2 that is how you write it on calculator, hope it was helpful

Jul 01, 2009 | Texas Instruments TI-83 Plus Calculator

I don't get it but here some help with logs:

log x base y = log x / log y (when log x is default base 10 in calculators) and

log (x*y) = log x + log y

log (x/y) = log x - log y

the bases is default 10

hope it's helped

log x base y = log x / log y (when log x is default base 10 in calculators) and

log (x*y) = log x + log y

log (x/y) = log x - log y

the bases is default 10

hope it's helped

Feb 05, 2009 | Casio FX-300MS Calculator

Here something that would help you:

log x base y = log x / log y

log (x*y) = log x + log y

log (x/y) = log x - log y

so log 24 base 2 it's log 24 / log 2 etc.

and if i get right what you wrote x= 10 ^ ( 3 * (log 5) ) if no inverse it it's easy really Hope it's helped you.

log x base y = log x / log y

log (x*y) = log x + log y

log (x/y) = log x - log y

so log 24 base 2 it's log 24 / log 2 etc.

and if i get right what you wrote x= 10 ^ ( 3 * (log 5) ) if no inverse it it's easy really Hope it's helped you.

Oct 23, 2008 | Casio FX-260 Calculator

30 people viewed this question

Usually answered in minutes!

×